Vitreous Inflammation Associated with Intravitreal Anti-VEGF Pharmacotherapy - Agrawal, Shivi; Joshi, Malav; Christoforidis, John B. (Mediators of Inflammation, 2013)
Vascular endothelial growth factor (VEGF) is a potent promoter of angiogenesis involved in a wide variety of physiologic processes. Intravitreal injections targeting VEGF have transformed the treatment of neovascular retinal diseases. Currently, there are four anti-VEGF agents in use: bevacizumab, ranibizumab, pegaptanib, and aflibercept. The success and frequency of anti-VEGF therapy have made the ocular safety profile of these agents of vital importance. This paper focuses on sterile endophthalmitis. In this paper, we compare the incidences of posttreatment sterile endophthalmitis among the four agents, review the mechanism of actions, and discuss the most prevalent hypotheses leading to sterile endophthalmitis.